Science capital as a lens for studying science aspirations – a systematic review - Kontkanen, Sini; Koskela, Teija; Kanerva, Oksana; Kärkkäinen, Sirpa; Waltzer, Katariina; Mikkila-Erdmann, Mirjamaija; Havu-Nuutinen, Sari (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
This article presents the findings of a systematic review that considers research conducted on science capital. Science capital includes what an individual knows about science, what they think about science, and who they know in science. These dimensions are related to science understanding in different cultural and social contexts and are affected to science aspirations. The research questions focus on how science capital is studied and contextualised and on what has been discovered about science capital. The materials were selected from three scientific databases using seven keywords. This article provides an overview of 32 selected articles published in peer-reviewed scientific journals from 2000-2021. The data were analysed using both qualitative data-driven and theory-guided content analyses. Although the review shows that science capital is studied using a diverse range of methods in different contexts, the studies have mainly focused on formal teaching and secondary and high school education in Europe, particularly on science-related social capital and subjective sense of self. The findings further reveal that the conceptual coherence of science capital still needs more accurate consideration to promptly explain its causes and consequences.